2020
DOI: 10.1111/1365-2664.13748
|View full text |Cite
|
Sign up to set email alerts
|

An ecosystem ecology perspective on artificial reef production

Abstract: 1. Artificial reefs are used around the world for many purposes, including widespread deployment to increase fishery yields. These reefs are well-studied from a direct fisheries-based perspective, drawing largely on traditional theory and methodological approaches from population and community ecology. 2. Here we provide an alternative perspective using basic tenets of ecosystem ecology. We focus largely on primary production, as this ecosystem process necessarily constrains the secondary production of fish an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 58 publications
(79 reference statements)
0
23
0
Order By: Relevance
“…As an important element in the restoration of the degraded coastal marine habitats, artificial reefs have been established globally to mimic the ecological functions of natural reefs (Baine, 2001;Carr and Hixon, 1997;Layman and Allgeier, 2020). It was reported that artificial reefs had a great effect on the diet of reef-associated fish species, especially on the upper trophic level species with great commercial and ecological values (Cresson et al, 2019;Lowry et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As an important element in the restoration of the degraded coastal marine habitats, artificial reefs have been established globally to mimic the ecological functions of natural reefs (Baine, 2001;Carr and Hixon, 1997;Layman and Allgeier, 2020). It was reported that artificial reefs had a great effect on the diet of reef-associated fish species, especially on the upper trophic level species with great commercial and ecological values (Cresson et al, 2019;Lowry et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, we concurrently note that we selected restoration sites based on historical knowledge and archived nautical maps to target sites where reefs were historically present but extracted entirely over the past decades. As such, this fundamental shift in reef availability likely rendered hard substrate to become a limiting factor for reef-associated fauna at the study area, implying substantial scope for productivity enhancement from reef construction over time (Folpp et al, 2020;Layman & Allgeier, 2020). We furthermore acknowledge that our results are based on a small number of reef replicates (two replicates per treatment) and that the study area of the Baltic Sea is characterized by unique conditions of low salinity levels and a multitude of anthropogenic stressors (Reusch et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…From there, more or less diverse communities will be developed depending on the characteristics of the site. If hydrodynamic conditions (currents and turbulence) and water quality (temperature and nutrients) permit it, some species will find sufficient calm and safety to use the barrier as a breeding area [16]. At the same time, the benthic colonization will begin; that is, the fixation and growth of algae and other species (polychaetes, bryozoans, barnacles, hydrozoans, ascites, among others).…”
Section: Ecological Functionmentioning
confidence: 99%
“…In this sense, the ecological performance will be evaluated specifically regarding the capacity of the artificial reef of providing habitat and producing a food chain in its surroundings. To do so, one of the main aspects to be evaluated is the artificial reef's capability of inducing or enhancing primary production [16]. In this sense, the surface roughness and presence of voids of the proposed artificial reef can be considered as having a good performance considering [45], where it is demonstrated that the incorporation of voids can lead to a larger area of the structure colonized by benthic species and that productivity rates of suspension feeders can be 2.4 times higher on artificial reefs constructed from complex blocks compared to reefs constructed from simple blocks (such as concrete cubes).…”
Section: Ecological Performancementioning
confidence: 99%